2011
DOI: 10.1111/j.1600-0781.2011.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Current sunscreen controversies: a critical review

Abstract: SummaryBackground/purpose: Sunscreens are believed to be a valuable tool in providing photoprotection against the detrimental effects of UV radiation, a known carcinogen. However, a number of controversies have developed regarding their safety and efficacy. This review summarizes the relevant studies surrounding these controversies. Methods: Evidence of the prevention of skin cancer, an oft-cited reason for sunscreen use, was examined as it pertains to squamous cell carcinoma, basal cell carcinoma and melanoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
164
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(177 citation statements)
references
References 94 publications
3
164
0
4
Order By: Relevance
“…Based on currently available information, the "harm" related to sunscreen use is probably not intrinsic to sunscreens 33 ; it is more likely related to the improper use of sunscreen, resulting in more sunburns. [7][8][9] Primary care providers who encourage the use of sunscreen should also instruct patients about the proper use of sunscreen to avoid sunburns.…”
Section: Discussionmentioning
confidence: 99%
“…Based on currently available information, the "harm" related to sunscreen use is probably not intrinsic to sunscreens 33 ; it is more likely related to the improper use of sunscreen, resulting in more sunburns. [7][8][9] Primary care providers who encourage the use of sunscreen should also instruct patients about the proper use of sunscreen to avoid sunburns.…”
Section: Discussionmentioning
confidence: 99%
“…The surface charge was modified with coating reagents, citrate for (-) charge (ZnO SM20(-) ), as reported previously. 6 On scanning electron microscopy, ZnO SM20(-) were determined to be an average of 29±3 nm and to be spherical in shape. The zeta potential of ZnO SM20(-) was -44.4±1.0 mV, with a negative surface charge.…”
Section: Materials and Methods Chemicals And Animalsmentioning
confidence: 99%
“…It is well known that both acute and chronic sun exposure induce biologically and clinically detrimental damaging effects such as sunburn, immunosuppression, photoaging and skin cancer [1][2]. Mironava et al [3] have reported that commercials compact fluorescent light (CFL) bulbs emit UV-A and UV-C light, which can induce to various types of skin cancer.…”
Section: Introductionmentioning
confidence: 99%